To analyses the Curriculum, Syllabi and Textbooks of English used in the schools (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The study investigates the correlation between English proficiency and access to higher education, employment opportunities, and social mobility. The study concludes with recommendations for curriculum improvements, teacher training programs, and policy reforms aimed at making English language education more accessible, inclusive, and impactful. This thesis contributes to the ongoing discourse on the role of English in education and its broader implications for students’ academic and professional growth in a rapidly evolving world.